2013
DOI: 10.1088/1751-8113/46/38/385002
|View full text |Cite
|
Sign up to set email alerts
|

Potts models with invisible states on general Bethe lattices

Abstract: Abstract.The number of so-called invisible states which need to be added to the q-state Potts model to transmute its phase transition from continuous to first order has attracted recent attention. In the q = 2 case, a Bragg-Williams, mean-field approach necessitates four such invisible states while a 3-regular, random-graph formalism requires seventeen. In both of these cases, the changeover from second-to first-order behaviour induced by the invisible states is identified through the tricritical point of an e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
7
19
0
Order By: Relevance
“…Here, we determine a more precise estimate for the value for q = 2, namely r c ≃ 3.65(5). This estimate is in excellent agreement with the z → ∞ limit of the result obtained for the Bethe lattice with z nearest neighbours [25]. We then considered the region 1 ≤ q < 2.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Here, we determine a more precise estimate for the value for q = 2, namely r c ≃ 3.65(5). This estimate is in excellent agreement with the z → ∞ limit of the result obtained for the Bethe lattice with z nearest neighbours [25]. We then considered the region 1 ≤ q < 2.…”
Section: Discussionsupporting
confidence: 85%
“…Rigorous results prove the existence of a first-order regime for any q > 0, provided that r is large enough [23,24]. Exact results for the value of r c for the model are known for a Bethe lattice [25] too.…”
Section: Introductionmentioning
confidence: 87%
“…The multispin extension of this model possesses a re-entrant phase transition and is in good agreement with experimental observations for polymer transitions [31,32]. The (2, r)-state Potts model without external fields is equivalent to the Blume-Emery-Grifiths (BEG) model [19,33,34] with a temperature dependent external field. Furthermore, the general q and r case can be interpreted as a diluted Potts model [19,29] …”
Section: Introductionsupporting
confidence: 82%
“…This model was originally suggested to explain why the phase transition with the q−fold symmetry breaking undergoes a different order than predicted theoretically [7,8,9]. Analysis of this model on different lattices has been a subject of intensive analytic [10,11,12,13,14,15,16] and numerical [7,8,9] studies. It has been shown that the number of invisible states (r) plays the role of a parameter, whose increase makes the phase transition sharper.…”
Section: Introductionmentioning
confidence: 99%